Hydrodinamic simulation model at Awana Porto Malai, Langkawi during spring tide - Mohd Arish, Nur Aini; Hamidon, Nuramidah; Tuan Ismail, Tuan Noor Hasanah; Harun, Hasnida; Hashim, Nor Haslina; Abdullah, Nor Maizzaty; Awang, Zarizi (Penerbit UTHM, 2020)
A using of hydrodynamic modelling whether physically or mathematics is a method that are very important to explaining phenomena which occurred in coast and represent dynamic comprehensive in detail. Apart from that, numerical calculation models also can be used for simulate current, water level and sediment transport and salinity [1]. There are some methods to understand hydrodynamic tide, which is numeric model. The using of numeric model is much cheaper compared to direct survey from field or develop hydraulic model.